Strategy to Increase Sharia Banking Performance through Value-added Creation Intellectual - Didit Supriyadi (Jurnal Keuangan dan Perbankan, 2022)
Based on the continuous flourishing of Sharia banking all over the globe, the current study aims to examine the impact of various factors on Sharia banking performance. These factors include cost efficiency, financial risks, funding, board characteristics, environmental analysis, and strategic value-added creation intellectual. A quantitative research methodology with a survey technique was employed to collect 421 respondents' data from 33 financial institutions, including 20 Sharia business units and 13 Sharia commercial banks. Descriptive analysis and structural equation modeling were performed in SmartPLS 3.0 software. The findings revealed the significant positive impact of environmental analysis on board characteristics, financial risk, cost efficiency, and funding. Likewise, results revealed the significant impact of board characteristics on financial risks, cost efficiency, funding, and value-added creation intellectual. Strategic value-added creation intellectual was found to positively impact the performance of Sharia banking in Indonesia. Except funding that has a moderate influence on Sharia banking performance, all other variables reflected the strong presence and impact on Sharia banking performance. The current study is novel in the existing body of literature by introducing this strategic value-added creation intellectual as a predictor of Sharia banking performance in Indonesia, along with the impacts of various other factors. Theoretically, the current study adds to the body of literature by providing a comprehensive framework related to the factors that impact Sharia banking performance. Moreover, based on the study results, the banks should keep a fair track of their capital and returns to enhance their performance. Simultaneously, it helps Sharia banks identify the significance of winning the investors' confidence by providing them security and catering to their needs cost-effectively.